FROM ACADEME TO INDUSTRY: WHICH ACADEMIC SKILLS MATTER? - Bartolata, Jocelyn I. (PEOPLE: International Journal of Social Sciences, 2016)
The paper explores the baffling question on which academic skills really matter on the job. And which don’t matter? The answer is derived from a survey of 86 students who underwent Language Practicum (LP) and 30 supervisors. LP is the On-the-Job Training (OJT) component of the Bachelor of Arts in English of the College of Arts and Letters, Bicol University. Because more demanding requirements and higher standards are required for the meaning of evaluation theory as a framework, the term model/approaches is preferred. This refers to “an evaluation theorist’s idealized conceptualizations for conducting program evaluation” (Stufflebeam and Shinkfield, 2013). As revealed in the findings, the academic skills found by the Language Practicum trainees to be most applicable to job performance are interpersonal skills and business letter writing. At the tail end are academic skills developed mostly from literature courses, Physical Education, Foreign language and Technological Environment. Organizational communication and interpersonal skills were rated by the sponsoring agencies to be the most useful academic skills needed during the training, and therefore in the trainees’ future jobs. Literature-related skills and physical education skills are least useful. To conclude: there are academic skills that are most and least useful to actual job performance. It is recommended that these be considered in the crafting of future curriculum to ensure that graduates are job-read.